2017
DOI: 10.1111/1468-0009.12247
|View full text |Cite
|
Sign up to set email alerts
|

Information Blocking: Is It Occurring and What Policy Strategies Can Address It?

Abstract: Congress has expressed concern about electronic health record (EHR) vendors and health care providers knowingly interfering with the electronic exchange of patient health information. These “information blocking” practices would privately benefit vendors and providers but limit the societal quality and efficiency benefits from EHR adoption. We found that information blocking is reported to frequently occur among EHR vendors as well as hospitals and health systems, and that it is perceived to be motivated by op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 8 publications
0
41
0
Order By: Relevance
“…The biggest roadblock for data sharing is the treatment of data as a commodity that can provide a competitive advantage. Therefore, sometimes both providers and vendors intentionally interfere with the flow of information to block the information flow between different EHR systems [31].…”
Section: Data Sharingmentioning
confidence: 99%
“…The biggest roadblock for data sharing is the treatment of data as a commodity that can provide a competitive advantage. Therefore, sometimes both providers and vendors intentionally interfere with the flow of information to block the information flow between different EHR systems [31].…”
Section: Data Sharingmentioning
confidence: 99%
“…Deliberate "information blocking" practices by EHR vendors and providers where they knowingly interfere with electronic exchange of health information for competitive purposes can also impede HIE use [31]. Ambulatory clinics could be coerced into implementing systems and document exchange practices by larger providers or vendors [32]. Recent Federal efforts aimed at implementing and improving interoperability standards are moving in the right direction to promote HIE use by clinical providers.…”
Section: Discussionmentioning
confidence: 99%
“…In a national survey of leaders in health information exchange, 50% of leaders reported that their EHR vendor participated in blocking practices, preventing appropriate information exchange. 70 Integration of the problem opioid users with a prescription opioid database/monitoring system may help further increase the utility of NLP. 49 Another concern that remains is that of security with regard to de-identification of data for data sharing.…”
Section: Commentary On Future Trendsmentioning
confidence: 99%